The Impact of Oil Prices on the Import of Capital Goods in Azerbaijan - Ahmadov, Baghish (International Journal of Energy Economics and Policy, 2024)
The article studies theoretical and practical aspects of the oil prices impact on the import of capital goods in an oil-exporting country. Based on the two-step Engel-Granger procedure for cointegration analysis, the relationship between the real volume of imported capital goods per capita and the real price of Azeri light oil is examined. It has been determined that the real volume of imported capital goods per capita is highly dependent on the oil price, and the volatility of the oil price also affects the volatility of imports of capital goods. This also shows that investment activity in the country depends on oil prices. Therefore, it is necessary to spend oil revenues, regardless of oil prices, depending on the economic development goals and to pursue policies to transform oil revenues into stable growth factors.